Penanganan Pascapanen dengan Pengeringan Daging Udang - Ryana Tammi Putri (abe.fp.unila.ac.id, 2026)
Shrimp is a leading fishery export commodity that is perishable. Proper post-harvest handling is crucial to maintain quality and prevent export rejections. This study aims to determine the handling of shrimp by drying until the moisture content approaches the equilibrium moisture content. The method used is an experimental method with temperature treatments of 40, 50, 60, 70 oC and room temperature. The results showed that drying at a temperature of 70 oC resulted in a faster decrease in moisture content. The equilibrium moisture content was reached more quickly compared to the drying temperature of 40 oC. Drying shrimp meat will increase the brightness of the shrimp meat, the reddish color and the yellowish color of the shrimp meat. The proximate value of shrimp meat before and after drying was relatively unchanged.